The passion of al-Hallaj : Mystic and Martyr of Islam. - Massignon, Louis, 1883-1962.; Mason, Herbert (Princeton : Princeton University Press, 1994)
Abridged from the four-volume The Passion of al-Hallaj, one of the major works of Western orientalism, this book explores the life and teaching of a famous tenth-century Sufi mystic and martyr, and in so doing describes not only his experience but also the whole milieu of early Islamic civilization. Louis Massignon (1883-1962), France's most celebrated Islamic specialist in this century and a leading Catholic intellectual, wrote of a man who was for him a personal inspiration. From reviews of the four-volume translation
Organization of a Postal System between Tustar and Baghdad -- The Incidents at Basra -- The ""Swelling Room"" (Bayt al-'Azama) -- The Account of Abu Musa 'Imran-b-Musa -- The Accounts of Ibn al-Jundi -- III. The Other Regions Traveled Through -- The Towns of Jibal -- Dinawar and Nihawand -- Hamadhan -- Rayy -- Hallaj's First Arrest: ""Fi Mahiyat al-Jabal -- New Year's Day in Nihawand -- The Towns of the Dulafids: Isfahan, Qumm -- The Altercation in Isfahan -- The Towns of Khurasan -- Herat, Marw, and Balkh -- Nishapur -- Talaqan
Description based upon print version of record.
The Towns of Transoxiana (Mawaralnahr): Bukhara, Samarqand, Ush, Isfijab.
JSTOR
Keywords: Ḥallāj, al-Ḥusayn ibn Manṣūr, -- 858 or 859-922.; Ḥallāj, al-Ḥusayn ibn Manṣūr, -- 858 or 859-922; Sufis -- Biography; Soufis -- Biographies; Sufis; Biographies